Evaluation of the Independent Curriculum Policy: A Literature Review on Theoretical Foundations and Implementation Practices - Waly, Rini; Asmi, Nurul; Abdullah, Rahibun; Syafriadi, Syafriadi (Journal of English Language and Education, 2025)
This study aims to evaluate the Merdeka Curriculum policy through a literature review of its theoretical foundations and implementation practices in educational institutions. The Merdeka Curriculum represents an educational reform effort that promotes flexible, character-based, and student-centered learning approaches. Employing a Systematic Literature Review (SLR) method, this research analyzes scientific publications from 2020 to 2024. The findings reveal that the curriculum is grounded in strong philosophical underpinnings, particularly the ideas of Ki Hadjar Dewantara, humanistic education, and constructivist pedagogy. Despite its robust conceptual basis, implementation faces several challenges, including teacher readiness, leadership capacity, infrastructure limitations, and regional disparities. Some schools have successfully adopted differentiated instruction and character-building projects, especially when supported by transformative leadership and active teacher learning communities. However, the implementation gap remains significant, particularly in underdeveloped and remote areas. This study recommends strengthening context-based training, establishing responsive evaluation mechanisms, and fostering collaboration among schools, parents, and local communities. In conclusion, the success of the Merdeka Curriculum depends on adaptive policy support, full engagement of the educational ecosystem, and a strong commitment to equity in access to quality education.